From VUCA to sustainability: The mediating role of digital leadership and the moderating role of digital organizational culture in SMEs - Al-Yousuf, Skeena Yousuf H A; Ahmad, Wasim (Edelweiss Applied Science and Technology, 2026)
This paper discusses how external VUCA, such as volatility, uncertainty, complexity, and ambiguity, influence digital leadership and how digital leadership supports sustainable performance in small and medium-sized enterprises (SMEs). Based on data gathered from SME managers and analyzed using PLS-SEM, the findings reveal that all four VUCA dimensions have a significant negative impact on digital leadership, indicating that environmental turbulence limits leaders' capacity to initiate digital transformation. Digital leadership has a high positive impact on sustainable performance which shows the position of digital leadership as a leading factor that boosts outcomes of innovation, operational efficiency and sustainability. Additionally, digital organizational culture acts as an important moderator in the relationship between digital leadership and sustainable performance, suggesting that cultural preparedness enhances leadership effectiveness. The results contribute to the understanding of VUCA and digital transformation by establishing the connection between environmental context, leadership capacity, and organizational culture as an integrated system. Practical implications emphasize the importance of capability building, cultural strengthening, and strategic resilience to help SMEs maintain performance in dynamic environments.